Reversal of Dopaminergic Degeneration in a Parkinsonian Rat following Micrografting of Human Bone Marrow-Derived Neural Progenitors - Aleksandra Glavaski-Joksimovic; Tamas Virag; Qin A. Chang; Neva C. West; Thomas A. Mangatu; Michael P. McGrogan; Millicent Dugich-Djordjevic; Martha C. Bohn Ph.D. (Cell Transplantation, 2009)
Parkinson's disease (PD) is a common neurodegenerative disease characterized by the selective loss of dopaminergic (DA) neurons in the midbrain. Various types of stem cells that have potential to differentiate into DA neurons are being investigated as cellular therapies for PD. Stem cells also secrete growth factors and therefore also may have therapeutic effects in promoting the health of diseased DA neurons in the PD brain. To address this possibility in an experimental model of PD, bone marrow-derived neuroprogenitor-like cells were generated from bone marrow procured from healthy human adult volunteers and their potential to elicit recovery of damaged DA axons was studied in a partial lesion rat model of PD. Following collection of bone marrow, mesenchymal stem cells (MSC) were isolated and then genetically modified to create SB623 cells by transient transfection with the intracellular domain of the Notch1 gene (NICD), a modification that upregulates expression of certain neuroprogenitor markers. Ten deposits of 0.5 μl of SB623 cell suspension adjusted from 6,000 to 21,000 cells/μl in PBS or PBS alone were stereotaxically placed in the striatum 1 week after the nigrostriatal projection had been partially lesioned in adult F344 rats by injection of 6-hydroxydopamine (6-OHDA) into the striatum. At 3 weeks, a small number of grafted SB623 cells survived in the lesioned striatum as visualized by expression of the human specific nuclear matrix protein (hNuMA). In rats that received SB623 cells, but not in control rats, dense tyrosine hydroxylase immunoreactive (TH-ir) fibers were observed around the grafts. These fibers appeared to be rejuvenated host DA axons because no TH-ir in soma of surviving SB623 cells or coexpression of TH and hNuMA-ir were observed. In addition, dense serotonin immunoreactive (5-HT-ir) fibers were observed around grafted SB623 cells and these fibers also appeared to be of the host origin. Also, in some SB623 grafted rats that were sacrificed within 2 h of dl -amphetamine injection, hot spots of c-Fos-positive nuclei that coincided with rejuvenated dense TH fibers around the grafted SB623 cells were observed, suggesting increased availability of DA in these locations. Our observations suggest that NICD-transfected MSC hold potential as a readily available autologous or allogenic cellular therapy for ameliorating the degeneration of DA and 5-HT neurons in PD patients.